Natural products in chemical biology - Civjan, Natanya (Hoboken, N.J. : Wiley, 2012)
"Based on the award winning Wiley Encyclopedia of Chemical Biology, this book provides a general overview of the unique features of the small molecules referred to as "natural products", explores how this traditionally organic chemistry-based field was transformed by insights from genetics and biochemistry, and highlights some promising future directions. The book begins by introducing natural products from different origins, moves on to presenting and discussing biosynthesis of various classes of natural products, and then looks at natural products as models and the possibilities of using them in medicine"--
"This book provides a fairly general overview of the unique features of the small molecules referred to as Natural Products, explores how this traditionally organic chemistry-based field was transformed by insights from genetics and biochemistry, and highlights some promising future directions"--
Chemical Diversity of Natural Products. Plant Natural Products / A Leslie Gunatilaka -- Marine Natural Products / Nobuhiro Fusetani -- Microbial Natural Products / Sergio Sanchez, Silvia Guzmn-Trampe, Mariana Avalos, Beatriz Ruiz, Romina Rodriguez-Sanoja, Manuel Jimenez-Estrada -- Biosynthesis of Natural Products. Nonribosomal Peptides / Georg Schoenafinger, Mohamed A Marahiel -- Plant Terpenoids / Christopher I Keeling, Jorg Bohlmann -- Polyketides in Fungi / Thomas J Simpson, Russell J Cox -- Modular Polyketide Synthases / Tonia J Buchholz, Jeffrey D Kittendorf, David H Sherman -- Polyketide Polyethers / Alison M Hill -- Alkaloids / Sarah E O'Connor -- Cofactors / Ilka Haase, Markus Fischer, Adelbert Bacher, Wolfgang Eisenreich, Felix Rohdich -- Antibiotics / Sergey B Zotchev -- Natural Products in Medicine. Pharmaceuticals: Natural Products and Natural Product Models / Sheo B Singh -- Natural Products as Anticancer Agents / David G I Kingston, David J Newman -- Plant-Derived Natural Products Research in Drug Discovery / Kuo-Hsiung Lee, Hideji Itokawa, Toshiyuki Akiyama, Susan L Morris-Natschke.
Includes bibliographical references and index.
Print version record.
Keywords: Biological products; Natural products; Biochemistry; Biological products; Natural products; Biochemistry; SCIENCE -- Life Sciences -- Biochemistry; Biochemistry; Biological products; Natural products; Biological products; Natural products; Biochemistry; Electronic books